Dupliek: Geringe kritiektolerantie - Bert Laeyendecker (Religie & Samenleving)
In Dols’ view it is important to tell his readers who and what kind of person Laeyendecker is. Therefore he introduces the concept ‘Standort’ and paints in full colors an engaged sociologist of religion versus himself as a open-minded, unbiased and detached researcher. The suggestion is clear. Unfortunately he neglects the fact that the Standort-discussion in sociology, history and philosophy has mostly led to denying the importance of the social position of an author for assessing the validity of his or her conclusions. Only the arguments are decisive for that. Therefore it would have been sufficient for me to see what he has to say about the critical remarks in my review. Nevertheless I have paid extensively attention to his description of my Standort for the simple reason that it contains a lot of mistakes. That takes the bigger part of my rejoinder, also because he has dissapointedly little to say about my arguments in the review.